Corrosão de estruturas metálicas em águas e sua proteção - Gasparoni, Amanda (2020)
This book was born from the elaboration of the Course Conclusion Work of the then academic student of Chemical Engineering, from the Federal University of Pampa (UNIPAMPA - Campus Bagé / RS), Amanda Gaddi Gasparoni under the guidance of the professor, Luciana Machado Rodrigues. The work presents a study on the phenomenon of Corrosion in carbon steel structures subjected to contact with water from different sources, and investigates a form of protection against corrosion. The study indicates sea water as the medium that produced the highest corrosion rate of carbon steel, being classified as highly aggressive corrosion, after a period of 90 days of exposure. The waters from the lake, artesian well and brook promoted moderate corrosion to steel, while treated water (drinking water) was the least aggressive medium, causing a low level of attack on the metal. The pure caffeine substance has been tested as a natural corrosion inhibitor of carbon steel. The coatings synthesized with the addition of caffeine promoted the protection of the metal exposed to sea water. It was concluded that it is possible to protect carbon steel metallic structures in an aqueous saline medium by using an organic coating with added caffeine, increasing the metal's protection time, generating a low environmental and health impact.